Conversation Analysis and genre theory - Ayaß, Ruth (Frontiers in Sociology, 2023)
Since its genesis in the 1960s, Conversation Analysis (CA) has noticeably developed further in terms of its subjects and methods. Its analyses, today, not only focus on conversations in the original sense, but also on visual elements such as gazes in interactions and the role of bodies. However, it also analyzes especially larger communicative units, e.g. in institutionalized settings and it addresses larger sequences of action. One of these approaches is the theory and analysis of communicative genres. Communicative genres are to be understood as consolidated forms of communication. The theory of communicative genres understands these forms as solutions to communicative problems. Genre analysis is methodologically grounded in CA; however, it exceeds it conceptually and theoretically, thus anchoring its questions clearly within sociology. The paper starts out by outlining the concepts and theory of communicative genres. The article discusses the empirical contribution of genre analysis using the example of three so-called “families of genres” families. The examples discussed are reconstructive genres (speaking about the past), genres of moral communication (speaking about other people’s behavior), and projective genres (speaking about the future). Using examples from empirical research, it is shown which communicative problems these genres solve. The paper finally considers the insights to be gained from genre analysis for sociology and CA.